To Determine the Effect of Using a Complete Feed Containing Protected Soybean Groats in the Production of Javanese Thin-Tailed Male Sheep Carcasses - Yahya Nor Arif; Nurul Fatimah Isnaniyah; Ahmad Pramono; Joko Riyanto (Buletin Peternakan, 2022)
The present study aims to determine the impact of complete feed containing protected soybean meal on the production of male thin-tailed lamb carcasses. A total of 15 (23.43 ± 1.40 kg) 12 months old male Thin-Tailed Sheep (TTL) were given 3 treatments and 5 replicates in a completely randomized design. The ration consisted of complete feed and formaldehyde-protected soybean groat (PSG). The treatments includes 100% complete feed (F1), 90% complete feed + PSG 10% (F2), and 80% complete feed + PSG 20% (F3). Data were analyzed using ANOVA and differences between treatments were further tested using Duncan’s New Multiple Range Test. The results indicated that the use of PSG containing complete feed did not improve the characteristics of carcasses (weight and percentage of carcass components, half-cuts and commercial cuts of carcass, fleshing index and meat bone ratio) of male TTLs (P>0.05). However, differences were found  in the rib eye muscle area. The use of complete feed containing 20% PSM (F3) resulted the highest rib eye muscle area figure compared to those of F2 and F1 (35.17 vs 27.00 and 26.33; P<0.05). Our study revealed that the use of complete feed containing 20% protected soybean groat resulted in higher rib eye muscle area by 25.14% compared to those containing no protected soybean groat. However, no differences in carcass characteristics were found in view of weight and percentage of carcass components, half cut and commercial carcass, fleshing index and meat bone ration in thin-tailed sheep.